Modeling the Impact of Human Population on the Dynamics of Atmospheric Carbon Dioxide (CO2) and Climate Change - Gupta, Rabindra Kumar (Journal of Nepal Mathematical Society, 2024)
A non-linear model is put forward and comprehended to understand climate change caused by change in the most abundance greenhouse gas CO2 due to the influence of human activities. The deterministic model (ODE) is followed by stochastic model (SDE) with the introduction of random noise to depict the more realistic situation as it includes environmental disturbances. Three state variables which are used in the model are human population, concentration of CO2, and forest biomass. It is formulated on the assumption that the concentration of atmospheric CO2 increases due to anthropogenic emissions as well as naturally when organisms respire, forest fire and volcano eruption. It also depletes naturally through nat ural sink (ocean, soil and plants). Equilibrium analysis and stability analysis of the model are performed. Numerical simulations are performed to justify the analytical results. The outcomes of the paper explain that the concentration of atmospheric CO2 can be lowered by minimizing the rate of use of forest biomass by human population which in turn slows down the growth of human population that ultimately reduces the anthropogenic emissions of CO2 gas. This decrement in the concentration of atmospheric CO2 gas controls the climate change